Analysis of the obliteration of the root canal: an investigation with Micro-CT - Victorino, Maria Luiza Zamparoni; Seron, Marcelo Augusto [UNESP]; Santin, Gabriela; Jussiani, Eduardo Inocente; Andrello, Avacir Casanova; Victorino, Fausto Rodrigo (FapUNIFESP (SciELO), 2024)
Introduction: Traumatized teeth may undergo calcific metamorphosis of the pulp, a factor which makes endodontic treatment difficult due to the total or partial obliteration of the root canal. Objective: To compare the existence of root canal lumen between Cone Beam Computerized Tomography and X-ray Microtomography in human teeth. Material and method: Ten single-rooted permanent teeth with some degree of obliteration observed in 2D radiographic images were selected. Cone Beam Computerized Tomography was performed, and the tomographic profile of root canal calcification was analyzed. The presence of root canal lumen was observed in the in the cervical, middle and apical thirds, and in the pulpal chamber, using scores from 1 to 5. The teeth were analyzed using X-ray Microtomography, and reconstructions were made using the NRecon software. The Friedman test with a significance level of 5% was used. Results: Notably, in the cervical region, the evaluators observed a low probability of the existence of lumen in the canal, using Cone Beam Tomography. However, the Micro-CT consistently identified the presence of canal lumen in this region. In the middle and apical regions, the probability of the existence of root canal lumen was confirmed among the evaluators at 100%, using Microtomography. A pattern of root canal obliteration from the crown to the apex was also observed in all specimens, and the canal lumen was confirmed using Microtomography images. Conclusion: It was evident that, for the endodontic treatment of cases with canals barely visible in the tomography, the probability of their existence is high.
Análise da obliteração do canal radicular: uma investigação com Micro-CT
Keywords: cone beam spiral computerized tomography; Endodontics; pathology